WEBVTT
00:00:01.270 --> 00:00:12.460
If π equals five minus three π and π equals negative two plus four π, find three times π plus π .
00:00:13.650 --> 00:00:20.910
To solve three times π plus π , weβll substitute π and π with their expressions.
00:00:22.160 --> 00:00:29.780
π is five minus three π plus π which is negative two plus four π.
00:00:30.550 --> 00:00:35.670
Keep the parentheses because weβre going to multiply this whole value by three.
00:00:36.630 --> 00:00:40.780
Now, inside the parentheses, weβre going to combine like terms.
00:00:41.670 --> 00:00:44.440
Weβll add five and negative two together.
00:00:45.150 --> 00:00:46.200
That equals three.
00:00:47.110 --> 00:00:51.810
We treat the π here like a variable, like any other variable.
00:00:52.060 --> 00:00:55.440
Negative three π can be combined with four π.
00:00:56.770 --> 00:00:58.370
And that would be one π.
00:00:59.270 --> 00:01:06.350
If youβre not sure what happened there, we had three negative πs and four positive πs.
00:01:06.990 --> 00:01:13.190
All of the negatives cancelled out and we were left with one remaining positive π value.
00:01:14.230 --> 00:01:19.130
Now, weβre going to need to multiply whatβs inside the parentheses by three.
00:01:19.950 --> 00:01:21.670
We do that by distributing.
00:01:22.170 --> 00:01:30.850
Three times three equals nine and three times one π or three times π equals three π.
00:01:31.870 --> 00:01:34.890
Our new expression is nine plus three π.